Board Diversity Terhadap Underpricing IPO dan Firm Value pada Perusahaan terdaftar di Bursa Efek Indonesia (BEI) - Rafi Altaf Tjaputra; Henny Setyo Lestari; Farah Margaretha (IPM2KPE, 2023)
This research aims to determine the effect of Board Diversity on IPO Underpricing and Firm Value in companies listed on the Indonesia Stock Exchange (BEI). This research method uses hypothesis testing method. Hypothesis testing in this research examines the influence of the variables Bsize, outside, AGE_SD, and woman on the underpricing and firm value variables. secondary data is data obtained indirectly. The data sources in this research were obtained from the BEI website (https://www.idx.co.id), investing.com website (https://www.investing.com). There are control variables, namely CAPEX, Age, leverage, ROA, size and new shares. The data used in this research is panel data, namely a combination of cross sectional and time series data on companies that conducted an IPO in 2017 on the IDX with observations for 5 years (2017 - 2021). In conclusion, that Board Size has no effect on IPO Underpricing and Board Size has a significant effect on Firm Value. Keywords : Board Diversity, Firm Value, IPO, Underpricing